Social Security Transfer Payments and Differences in State Per Capita Incomes, 1929, 1939, and 1949 - Schaller, Howard G. (The Review of Economics and Statistics, 1955)
8OCIAL security transfer payments have become an important segment of the income paid to individuals.' Primarily, the payments are designed to provide income continuity to those persons who have retired from the labor force because of age or are either unable to work or to find employment. Given this objective, the payments should flow to persons in the lower income groups.2 This paper attempts to measure the effects of the social security transfer payments on the differences in per capita incomes among the 48 states. Do the government programs which result in a set of payments designed to flow to the lower income groups also tend to equalize the geographic distribution of income? The use of the state distribution of income as a policy determinant and as a tool of economic analysis requires a thorough understanding of the forces with which the per capita income differences are associated. The present article isolates a specific type of payment for study and will add to the growing body of knowledge concerning the forces underlying the geographic income aggregates.3 I